The The Use of Cake Application in Learning English Speaking Skills - Aqilah, Drupadi Sana (Universitas Pendidikan Ganesha, 2023)
Technology is quite important to use in everyday lives in this modern day. Young learners nowadays use technology for study and it can assist teachers and students in carrying out learning tasks. There are various applications available right now that can help kids learn more effectively; one such app for learning to speak is the cake app. This study aims to analyze the use of Cake application as a tool to learn English speaking skills. A literature study was conducted in this research. A literature study is a data collecting strategy that comprises doing study studies of books, literature, records, and reports that have to do with issues solved. One of the most important abilities in learning English is speaking and a skill practiced in speaking is how to pronounce words properly and correctly. The Cake program is a tool for learning English. Playlist Corporation's Cake - Learn English for Free in the category of Education is developed by Playlist Corporation. There are several features in this application such as watching short movie and practicing speaking by using dialogue. The research's goal is to look into how Cake Application can be used to learn how to speak.